2022
DOI: 10.1186/s13293-022-00468-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the medial prefrontal cortical glutamate system

Abstract: Background Dysregulation in the prefrontal cortex underlies a variety of psychiatric illnesses, including substance use disorder, depression, and anxiety. Despite the established sex differences in prevalence and presentation of these illnesses, the neural mechanisms driving these differences are largely unexplored. Here, we investigate potential sex differences in glutamatergic transmission within the medial prefrontal cortex (mPFC). The goal of these experiments was to determine if there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 59 publications
2
17
3
Order By: Relevance
“…Importantly, the results of the present study indicate that feeding of dams with VOR- containing food at the dose that produces procognitive effects (Felice et al, 2018) and reverses cognitive impairments (Pehrson et al, 2018) does not result in adverse effects on excitatory synaptic transmission in offspring mPFC, in contrast to FLX. Besides, our recordings of layer II/III FPs in control mice do not confirm the notion that females express a higher level of glutamatergic transmission in the mPFC than males (Knouse et al, 2022), which was also based on recordings from layer V neurons.…”
Section: Discussioncontrasting
confidence: 97%
“…Importantly, the results of the present study indicate that feeding of dams with VOR- containing food at the dose that produces procognitive effects (Felice et al, 2018) and reverses cognitive impairments (Pehrson et al, 2018) does not result in adverse effects on excitatory synaptic transmission in offspring mPFC, in contrast to FLX. Besides, our recordings of layer II/III FPs in control mice do not confirm the notion that females express a higher level of glutamatergic transmission in the mPFC than males (Knouse et al, 2022), which was also based on recordings from layer V neurons.…”
Section: Discussioncontrasting
confidence: 97%
“…Some limitations of this study include differences between the two cohorts that may influence their forebrain projections, including gender mix and pre-injection history. Some evidence suggests that female gender affects mPFC (Knouse et al, 2022), although we have not found differences in previous work comparing MEMRI data between genders (Uselman et al, 2020). This result could have been due to a lower sensitivity to such gender-dependent effects in our methodology.…”
Section: Discussioncontrasting
confidence: 95%
“…The prefrontal cortex (PFC) provides top-down regulation of motivated behaviors and displays sex differences in form and function [10][11][12][13][14]. Most PFC neurons are glutamatergic pyramidal cells that send, receive, and integrate information to and from various subcortical and cortical structures [15,16].…”
Section: Introductionmentioning
confidence: 99%